Effects of the Cha1 Novel Combination Treatment on Tumor Properties and Immune Response in Triple Negative Breast Cancer - DeIeso-Frechette, Francesca H. (Tufts Archival Research Center, 2020)
Experiments at the Yee lab have shown that Cha1, a combination treatment of Epigallocatechin-3-gallate (EGCG) and 5-aza-2’-deoxycytidine (Decitabine, or DAC), can decrease metastases and tumor growth while increasing immune response in Triple Negative Breast Cancer (TNBC) in xenograft and syngeneic mouse models. TNBC is an aggressive form of breast cancer that, unlike other types of breast cancer, lacks overexpression of progesterone receptors, estrogen receptors, and HER2, making it extremely difficult to treat. Previously at the Yee lab, Cha1 has been shown to decrease tumor size, decrease metastases, and decrease Wnt/β-catenin signaling. This report shows the effects of the Cha1 treatment on tumor properties and immune response to the tumor. Cha1 could be a very promising treatment for TNBC in the future especially in combination with immune checkpoint inhibitors, which could work together with Cha1 to induce apoptosis of tumor cells, stopping tumor growth and metastasis, and possibly eliminating tumor cells entirely. Advisor: Dr. Mitch McVey.